2019
DOI: 10.1371/journal.pone.0212626
|View full text |Cite
|
Sign up to set email alerts
|

Composition of gut microbiota in patients with toxigenic Clostridioides (Clostridium) difficile: Comparison between subgroups according to clinical criteria and toxin gene load

Abstract: Data concerning the human microbiota composition during Clostridioides (Clostridium) difficile infection (CDI) using next-generation sequencing are still limited. We aimed to confirm key features indicating tcdB positive patients and compare the microbiota composition between subgroups based on toxin gene load ( tcdB gene) and presence of significant diarrhea. Ninety-nine fecal samples from 79 tcdB positive patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
49
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 45 publications
8
49
2
2
Order By: Relevance
“…We observed a lower microbial diversity for CDI + patients compared to healthy volunteers (Data not shown), con rming the results of previous studies [74]. As a considerable variability was found within each group of individuals, we corrected the individual effect in the statistical model to emphasize differences between extraction protocols.…”
Section: Quality and Quantity Of Extracted Dnasupporting
confidence: 89%
“…We observed a lower microbial diversity for CDI + patients compared to healthy volunteers (Data not shown), con rming the results of previous studies [74]. As a considerable variability was found within each group of individuals, we corrected the individual effect in the statistical model to emphasize differences between extraction protocols.…”
Section: Quality and Quantity Of Extracted Dnasupporting
confidence: 89%
“…We found C. difficile -positive samples to be enriched with members of the Escherichia, Bacteroides, Enterococcus and Parabacteroides genera, and C. difficile -negative samples with members of the Prevotella, Megamonas , and Streptococcus genera. Almost identical trends were found for taxa of the Escherichia, Parabacteroides, Enterococcus, Prevotella and Megamonas genera in one study comparing C. difficile non-colonized, asymptomatically colonized and infected human adults (19), and for taxa of the Parabacteroides, Prevotella, Paraprevotella and Enterococcus genera in another study of non-colonized and colonized adults (38). Similar findings were found for the Bacteroides genera in a study of human infants (39) .…”
Section: Discussionmentioning
confidence: 56%
“…Asymptomatic carriage of C. difficile is common in young animals of many species, including humans, dogs, pigs, and horses. In people, colonization with C. difficile has been shown to be associated with altered gut microbial diversity (17, 19, 3638), but no studies have examined this association in dogs. We found that the association between lower bacterial community diversity and C. difficile colonization was statistically significant even when accounting for age, and certain bacterial taxa were preferentially associated with C. difficile colonization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Le nombre d'espèces présentes dans le microbiote des patients atteins d'infection récidivante à Cd est diminuée d'environ 40 % par rapport aux individus sains(35). L'abondance de plusieurs genres bactériens constitutifs du "core microbiome", c'est-àdire l'ensemble des espèces présentes chez tous les individus sains, est considérablement diminuée(36). La TMF restaure la diversité du microbiote intestinal ainsi que son effet barrière contre la colonisation par des pathogènes et permet ainsi une amélioration clinique dans 80 à 90 % des cas et une rémission complète un mois après l'intervention dans 60 % des cas(37- 39).…”
unclassified